Attire insensitive person re-identification - Leong, Zaccheus Yu Hao (Nanyang Technological University, 2023)
Person re-identification is the matching images of people across disjoint camera views in a multi-camera system. It is useful for public security applications where a watchlist of known people is provided as the target set for searching through a large volume of video surveillance footage where the people on the watchlist are likely to re-appear. In some events (eg., sports events) and locations (eg., central business district), many pedestrians may wear similar clothes (eg. sports uniforms, business suits). Re-identifying a person from a crowd with similar clothing, or the same person at different times in different attire, are challenging problems.